MODEL PERKEMBANGAN PENYAKIT BULAI PADA BERBAGAI VARIETAS DI KABUPATEN MOJOKERTO - Khansa Amara; Herry Nirwanto; Wiwik Sri Harijani; Latief Imanadi (UPN VETERAN JAWA TIMUR, 2020)
Peronosclerospora spp. is one of the problems in the cultivation of maize in Indonesia. Damage caused by the fungus Peronosclerospora spp. can reach 90-100% especially in susceptible varieties. Abiotic environmental conditions such as low temperatures and high humidity accompanied by a layer of water on the leaf surface can increase the occurrence of disease. Disease management techniques are still dominated by the application of synthetic fungicides that have several negative impacts, such as killing non-target organisms, increasing pathogen resistance and environmental pollution. However, these impacts can be suppressed through monitoring activities that play a key role in integrated disease management programs. Monitoring activities facilitate the process of epidemiological analysis through a mathematical model approach so that it can be known patterns of development of plant diseases and the rate of infection as a basis in developing disease management strategies. Therefore, it is necessary to conduct research on disease development models ranging from maize varieties in the improvement of maize plants in Mojokerto Regency. The results showed a model that was able to represent the development of downy mildew in Mojokerto was monit. The highest infection rate was on land using P35 variety from other land using NK 6172 variety.